LIPID METABOLISM FEATURES IN PATIENTS WITH THE COMBINATION OF NON-ALCOHOLIC STEATOHEPATITIS AND ITS CORRECTION - Filippova, O.Yu. (World of Medicine and Biology, 2019)
The purpose of the study was to estimate the effects of different treatment regimens on lipid metabolism in patients with non-alcoholic steatohepatitis (NASH) in combination with obesity (OB) and pathology of the biliary tract (BT) according to the 6-month dynamic observation. A dynamic study of 100 patients with NASH in combination with OB and BT pathology was performed, including the lipid metabolism indices study. It was found that lipid metabolism disorders occurred in all groups of patients, being characterized by an increase in triglycerides, cholesterol of low density lipoproteins, and disorders of metabolism and transport of the total cholesterol and reduced cholesterol levels of high density lipoproteins in comparison with apparently healthy individuals (from p